Toxicological Responses of Confused Flour Beetle, Tribolium confusum du Val (Coleoptera: Tenebrinoidea) to various Isothiocyanate Compounds - Demirel, N.; Kurt, S.; Gunes, U.; Uluc, F.T.; Cabuk, F. (Asian Journal of Chemistry, 2010)
The confused flour beetle, Tribolium confusum du Val (Coleoptera: Tenebrionidae), is one of the most serious pests of stored cereals. The phenyl isothiocyanate resulted in significant mortality on the confused flour beetle with 0.1 and 0.2 μL concentrations in both bioassays, respectively. Allyl (2-propenyl) and methyl isothiocyanate caused significant mortality with 0.2 μL concentration in the first bioassay. In the following bioassay, methyl isothiocyanate resulted in significant mortality with 0.1 and 0.2 μL concentarions. In addition, allyl (2-propenyl) and ethyl isothiocyanate had significant mortality with 0.2 μL concentration. Phenyl isothiocyanate had the lowest LC50 (0.02781, 0.02627) and highest toxicity on the confused flour beetle in both bioassays. In the first bioassay, phenyl isothiocyanate were followed by allyl (2-propenyl) (LC50: 0.05262) and methyl isothiocyanate (LC50: 0,07178) toxicities. In the following bioassay, phenyl isothiocyanate were followed by methyl isothiocyanate (LC50: 0.04494) and allyl (2-propenyl) (LC50: 0.06342) toxicities. Ethyl isothiocyanate had the higest LC50 (0.12408) and LC50 (0.09989) and lowest toxicities on the confused flour beetle in both bioassays. In conclusion, phenyl isothiocyanate (0.1, 0.2 μL) concentrations, allyl (2-propenyl) and methyl isothiocyanate (0.2 μL) concentration suggest as an insect fumigants to control the confused flour beetle in stored cereals.